2000
DOI: 10.1128/.68.11.6182-6188.2000
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of the Capsular Polysaccharide C Biosynthesis Region of Bacteroides fragilis

Abstract: A genetic approach was used to assess the heterogeneity of the capsular polysaccharide C (PS C) biosynthesis locus of Bacteroides fragilis and to determine whether distinct loci contain genes whose products are likely to be involved in conferring charged groups that enable the B. fragilis capsular polysaccharides to induce abscesses. A collection of 50 B. fragilis strains was examined. PCR analysis demonstrated that the genes flanking the PS C biosynthesis region are conserved, whereas the genes within the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In addition, not all non-enterotoxigenic strains ameliorate DSS-induced colitis and some strains even skew macrophages to take on a pro-inflammatory M1-phenotype 18,32 . Furthermore, capsular polysaccharides are distinct between strains of Bacteroides fragilis 33 . We have shown that between B. fragilis strains, the genetic composition of PAP B. fragilis p207 and strain 9343, are genetically-distinct, suggesting that they may have distinct immunomodulatory properties (Figure S6).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, not all non-enterotoxigenic strains ameliorate DSS-induced colitis and some strains even skew macrophages to take on a pro-inflammatory M1-phenotype 18,32 . Furthermore, capsular polysaccharides are distinct between strains of Bacteroides fragilis 33 . We have shown that between B. fragilis strains, the genetic composition of PAP B. fragilis p207 and strain 9343, are genetically-distinct, suggesting that they may have distinct immunomodulatory properties (Figure S6).…”
Section: Discussionmentioning
confidence: 99%